PENERAPAN MEDIA GAME EDUKASI (KARTU SERU) PADA PEMBELAJARAN BAHASA ARAB DI MTS DARUSSALIHIN BERRU - Masnah; Yusring Sanusi Baso; Muhammad Ridwan (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2024)
This research is motivated by the Kartu Seru learning media which has never been applied in Arabic language learning at Mts Darusshalihin Berru. The purpose of this study was to determine the effect of the application of educational game media (Kartu Seru) in improving vocabulary skills of Arabic language learning at MTs Darusshalihin Berru. This research approach is a quantitative approach with experimental research type. This research design used one group pretest-posttest design. The population in this study were all students of Madrasah Tsanawiyyah Darusshalihin Berru class VIII consisting of class VIII A, VIII B, and VIII C. Sampling using random sampling technique and resulted in class VIII A as the experimental class and class VIII B as the control class. The type of instrument used is a pretest and posttest question of student learning outcomes totaling 30 questions with 10 matching questions with 20 multiple choice questions. The results showed that the experimental class experienced an increase in mastery of Arabic vocabulary (mufradat) with a higher percentage value than the control class. This is evidenced by the average value of class VIII B (control class) of 57.8% (pre-test) and 50.8% (post-test). The average value of class VIII A (experimental class) in percentage units is 63.4% (pre-test) and 92.2% (post-test). These results show that the application of educational games (Kartu Seru) in Arabic language learning has an influence on student learning outcome and is effective to be used to achieve Arabic language learning objectives. Keyword : influence, educational game media kartu seru.